Ir4+-Doped NiFe LDH to expedite hydrogen evolution kinetics as a Pt-like electrocatalyst for water splitting - Chen, Qian-Qian; Hou, Chun-Chao; Wang, Chuan-Jun; Yang, Xiao; Shi, Rui; Chen, Yong (Chemical communications (Cambridge, England), 2018)
NiFe-layered double hydroxide (NiFe LDH) is a state-of-the-art oxygen evolution reaction (OER) electrocatalyst, yet it suffers from rather poor catalytic activity for the hydrogen evolution reaction (HER) due to its extremely sluggish water dissociation kinetics, severely restricting its application in overall water splitting. Herein, we report a novel strategy to expedite the HER kinetics of NiFe LDH by an Ir4+-doping strategy to accelerate the water dissociation process (Volmer step), and thus this catalyst exhibits superior and robust catalytic activity for finally oriented overall water splitting in 1 M KOH requiring only a low initial voltage of 1.41 V delivering at 20 mA cm−2 for more than 50 h.